An Approach to Overcome the Limitations of Surveillance of Asbestos Related Diseases in Low- and Middle-Income Countries: What We Learned from the Sibaté Study in Colombia - Juan Pablo Ramos-Bonilla; Margarita Giraldo; Daniela Marsili; Roberto Pasetto; Benedetto Terracini; Agata Mazzeo; Corrado Magnani; Pietro Comba; Benjamin Lysaniuk; María Fernanda Cely-García; Valeria Ascoli (Ubiquity Press, 2023)
Introduction: The asbestos industry began its operations in Colombia in 1942 with the establishment of an asbestos-cement facility in Sibaté, located in the Department of Cundinamarca. Despite extensive asbestos use and production in Colombia, the country lacks a reliable epidemiological surveillance system to monitor the health effects of asbestos exposure. The Colombian health information system, known as SISPRO, did not report mesothelioma cases diagnosed in the municipality, posing a significant challenge in understanding the health impacts of asbestos exposure on the population of Sibaté. Methods: To address this issue, an active surveillance strategy was implemented in Sibaté. This strategy involved conducting door-to-door health and socioeconomic structured interviews to identify Asbestos-Related Diseases (ARDs). Validation strategies included a thorough review of medical records by a panel of physicians, and the findings were communicated to local, regional, and national authorities, as well as the general population. Results: The active surveillance strategy successfully identified a mesothelioma cluster in Sibaté, revealing the inadequacy of the existing health information system in monitoring asbestos-related diseases. The discovery of this cluster underscores the critical importance of implementing active surveillance strategies in Colombia, where governmental institutions and resources are often limited. Conclusion: The findings of this study emphasize the urgent need for Colombia to establish a reliable epidemiological surveillance system for asbestos-related diseases (ARDs). Active surveillance strategies can play a crucial role in identifying mesothelioma clusters and enhancing our understanding of the health effects of asbestos exposure in low- and middle-income countries.